2008
DOI: 10.1111/j.1751-1097.2007.00277.x
|View full text |Cite
|
Sign up to set email alerts
|

Oligonol Inhibits UVB‐induced COX‐2 Expression in HR‐1 Hairless Mouse Skin—AP‐1 and C/EBP as Potential Upstream Targets

Abstract: Oxidative stress and inflammatory tissue damage are two major events frequently implicated in carcinogenesis. Numerous polyphenolic compounds derived from plants possess antioxidant and anti-inflammatory activities and are hence effective in preventing cancer. Oligonol is a polyphenol formulation enriched with catechin-type oligomers. As an initial approach to assess the chemopreventive potential of oligonol, we have determined its effects on inflammatory as well as oxidative damage in mouse skin irradiated wi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
19
0

Year Published

2009
2009
2018
2018

Publication Types

Select...
9

Relationship

3
6

Authors

Journals

citations
Cited by 34 publications
(19 citation statements)
references
References 52 publications
0
19
0
Order By: Relevance
“…It has been shown that Oligonol is readily absorbed from intestines, and has a strong antioxidative activity and ability to prevent photocarcinogenesis (Kundu et al, 2008). Regarding lipid metabolism and obesity, Oligonol promotes adiponectin production in rat visceral fat cells in conjunction with a reduction of triacylglycerol accumulation .…”
Section: Discussionmentioning
confidence: 99%
“…It has been shown that Oligonol is readily absorbed from intestines, and has a strong antioxidative activity and ability to prevent photocarcinogenesis (Kundu et al, 2008). Regarding lipid metabolism and obesity, Oligonol promotes adiponectin production in rat visceral fat cells in conjunction with a reduction of triacylglycerol accumulation .…”
Section: Discussionmentioning
confidence: 99%
“…Stimulation of HR-1 [14, 15, 18, 19] and SKH-1 [20] hairless mouse skin with UVB resulted in a significant increase in COX-2 expression and conversely topical application of sulforaphane [14], γ -tocotrienol [15], anthocyanins from black soybean seed coats [18], oligonol [19], and proanthocyanidins from grape [20] inhibited UVB-induced COX-2 expression.…”
Section: Discussionmentioning
confidence: 99%
“…Based on recent studies, there is accumulating evidence that oligonol can induce some physiological and biochemical alterations in vitro and in vivo, such as the induction of apoptosis in cancer cells (23), antioxidant and anti-inflammatory effects in mice (24), and beneficial subjective effects on the feeling of fatigue in young athletes (67). Moreover, the oral administration of oligonol improves the regulation of genes for adipokines in white adipose tissue of mice on administering a high-fat diet (26).…”
Section: Resultsmentioning
confidence: 99%
“…This method involves binding a compound possessing a phloroglucinol ring structure (such as catechin) as a nucleophilic compound to proanthocyanidin fragmented under acidic conditions. As shown in Figure 1 (23) as well as antioxidant and anti-inflammatory effects (24), beneficial activity for nitric oxide bioavailability (25), and a regulatory effect on lipid metabolism (26,27). Indeed, dietary feeding with proanthocyanidins, which comprise oligonol, has been reported to induce a significant attenuation of tissue fat levels, without changing the total body mass of the animals compared with non-proanthocyanidin-fed animals (28).…”
Section: Conversion To Low-molecular-weight Proanthocyanidinmentioning
confidence: 99%